Pengaruh Person Job Fit Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Pegawai Di Dinas Lingkungan Hidup Kabupaten Cirebon - Al Amachdi; Wiwi Hartati; Sylvani Sylvani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of Person Job Fit and Non-Physical Work Environment on the performance of civil servants at the Environmental Service Office of Cirebon Regency. The background of this research is the problem of fluctuating employee performance, the mismatch between individual characteristics and job demands, as well as the perception of an insufficiently supportive non-physical work environment. This study employs a quantitative method, with a population of 75 employees, and uses a saturated sampling or census technique for sampling. Data collection techniques include observation, interviews, and questionnaires. Data were analyzed using multiple linear regression tests to examine the influence of each variable, with the help of SPSS 25. The results show that Person Job Fit has a positive and significant effect on employee performance. Similarly, the Non-Physical Work Environment also has a positive and significant effect on employee performance. Furthermore, simultaneously, both variables have a significant effect on employee performance. These findings reinforce the importance of aligning individuals with their jobs (Person Job Fit) and establishing a harmonious Non-Physical Work Environment to enhance employee performance, particularly in the public service sector of the Environmental Service Office of Cirebon Regency.